Risk factors associated with Clostridium difficile infection after kidney and pancreas transplantation. Issue 5 (25th July 2013) - Shah, S.A.; Tsapepas, D.S.; Kubin, C.J.; Martin, S.T.; Mohan, S.; Ratner, L.E.; Pereira, M.; Kapur, S.; Dadhania, D.; Walker‐McDermott, J.K.
Abstract: Background: Clostridium difficile infection (CDI) is a common cause of nosocomial antibiotic‐associated diarrhea with an increased incidence reported in solid organ transplant recipients. We sought to determine if kidney and/or pancreas transplant recipients possess unique risk factors for CDI. Methods: Between January 2009 and February 2011, 942 kidney and 56 pancreas transplants were performed at the 2 centers. Of these, 28 recipients (kidney, n = 24; pancreas, n = 4) developed CDI. Cases were matched to controls ( n = 56) in a 1:2 ratio. Results: Those with CDI were mostly male patients (82% vs. 48%, P = 0.003), deceased‐donor organ recipients (86% vs. 64%, P = 0.045), more likely to have leukopenia (18% vs. 4%, P = 0.038), and had undergone a gastrointestinal procedure within 3 months preceding CDI diagnosis (18% vs. 4%, P = 0.038). Cases had higher cumulative and restricted antimicrobial exposure in days (37 ± 79 vs. 8 ± 12, P = 0.009 and 27 ± 69 vs. 7 ± 10, P = 0.032). Cephalosporin use was more common among cases (43% vs. 16%, P = 0.008). Conclusion: Careful antimicrobial selection and assurance of optimal treatment duration in the kidney and pancreas transplant population is prudent. Clinicians should have a heightened awareness of CDI risk particularly during periods of leukopenia and in the setting of gastrointestinal procedures.